Identifying the Commonalities between Lean Construction and LEED Requirements - Sadikoglu, Emel; Demirkesen, Sevilay; Zhang, Chengyi (Amer Soc Civil Engineers, 2022)
The construction industry is one of the largest industries creating energy and resources consumption at high levels as well as leading to greenhouse gas emissions. This generates negative impacts in economic, social, and environmental aspects. In order to mitigate these negative impacts, sustainable construction plays a crucial role. At this point, Lean strongly interacts with sustainable construction for the fact that these concepts have similar objectives such as reducing waste, maximizing value, increasing efficiency and productivity, and improving health and safety. A major portion of the studies have investigated the implementation of sustainability and Lean construction simultaneously, which created positive outcomes for the construction firms. In this study, Leadership in Energy and Environmental Design (LEED) is analyzed to reveal the impact of Lean practices in increasing project success when it is integrated with sustainable construction. In this respect, a systematic literature review is conducted to investigate the synergy between Lean construction and sustainability. For this purpose, a comparative matrix is structured to integrate Lean construction with the LEED certification processes. Commonalities are revealed to best reflect the level of interaction in between based on semi-structured interviews. This study indicates that Lean construction is strongly associated with sustainable construction and Lean has a strong potential of facilitating the achievement of LEED certification.
Construction Research Congress (CRC) on Project Management and Delivery, Contracts, and Design and Materials -- MAR 09-12, 2022 -- Via Dept Civil & Environm Engn, Vecellio Construct Engn & Management Progr, Arlington, VA
Keywords: Sustainable construction; LEED; Lean construction; integration